MENYOAL RAJAH DAN PASADUAN DALAM STRUKTUR TEKS CARITA PANTUN BADUY - Saparudin, Endin; Fitriyah, Atiqotul; Yoesoef, M.; Nariswari, Fitria Sis; Siagian, Alfian (Paradigma: Jurnal Kajian Budaya, 2025)
This article explores the text structure of Kanekes (Baduy) carita pantun, focusing on the presence of rajah, previously understood as the beginning and end of the text (functioning as 'prayers and supplications' to the ancestors). Through analysis of documentation from J.J. Meijer (1891), Wim van Zanten (1977), as well as recent fieldwork (2022-2023), it was found that the rajah was not always in this position. This research uses an ethnographic approach and was conducted in August-October 2022 and September-October 2023 in Kanekes, Leuwidamar, Banten. Nine informants who work as pemantun and responders were recruited. Data were obtained through interview and recording techniques in three agrarian rituals (rice planting, house inauguration, and marriage). Based on the field data, it is found that the text of Baduy carita pantun in the three rituals has a unique different structure, with the pasaduan element not at the beginning and end, but after bangbalikan/usualan. In addition, panunda (intermediary) repetition also plays an important role. This finding challenges previous views and shows the complexity of the Baduy carita pantuntext structure that is different from other Sunda Tatar regions. The results of this study contribute to the understanding of the patterns of carita pantun in Baduy community based on field data and carita pantun texts that have been collected by previous researchers (Pleyte, Zanten, and Rosidi); knowledge about the aspects of preserving intangible cultural heritage among the Baduy (Kanekes) community which can be illustrated through agricultural ritual activities routinely carried out; and this study illustrates the current condition of carita pantun in Baduy (Kanekes) in the midst of cultural changes in the supporting community.